Brief computer interventions enhance emergent academic skills in susceptible children: A gene-by-environment experiment. (October 2016) - Plak, Rachel D.; Merkelbach, Inge; Kegel, Cornelia A.T.; van IJzendoorn, Marinus H.; Bus, Adriana G.
Abstract: In this study we examined the potential of technology-enhanced educational programs for young children lagging behind in emergent literacy skills. Differential effects of technology-enhanced educational programs for poor performers were tested in a randomized controlled trial. Our previous study showed that children with a dopamine-related genetic polymorphism – DRD4 7-repeat – are more susceptible to their learning environment than children without this polymorphism, serving as a proxy for the dopamine-system related genetic pathway. In the current study, we aimed to replicate and extend these results in a sample of 583 kindergarteners from 136 schools. As predicted by the genetic differential susceptibility theory, carriers of the DRD4 7-repeat allele profited significantly from Living Books ( d = 0.75), whereas non-carriers did not benefit ( d = 0.02). Living Letters did not show a Gene × Environment interaction. We discuss why carriers of DRD4 7-repeat allele particularly benefit from Living Books . Highlights: RCT to test effects of educational computer programs for kindergarten. In particular the book reading program was effective for literacy delayed children. Specifically for a subsample of children who, due to their dopamine system, are very responsive to the environment.